2012
DOI: 10.1111/j.1755-3768.2011.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the fourth cranial nerve in congenital Brown syndrome

Abstract: . Purpose:  To elucidate the aetiology of congenital Brown syndrome. Methods:  Four consecutive patients diagnosed with unilateral congenital Brown syndrome had a comprehensive standardized ocular motility examination. Any compensatory head posture was measured. Brain magnetic resonance imaging (MRI) with regard for the IV cranial nerve (CN) was performed in all patients. Orbital MRI was performed in 2/4 patients, with images acquired in eight directions of gaze and superior oblique (SO) muscle areas compared.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Recently, it was proposed that congenital BrS could be regarded as a congenital cranial dysinnervation disorder (CCDD). 16,21,22 Ellis et al 22 reported three cases of congenital Brown syndrome without clinical SO palsy, who exhibited moderate to severe ipsilateral SO hypoplasia. They suggested that these congenital cases might represent CCDD due to absence of normal trochlear innervation and without misinnervation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was proposed that congenital BrS could be regarded as a congenital cranial dysinnervation disorder (CCDD). 16,21,22 Ellis et al 22 reported three cases of congenital Brown syndrome without clinical SO palsy, who exhibited moderate to severe ipsilateral SO hypoplasia. They suggested that these congenital cases might represent CCDD due to absence of normal trochlear innervation and without misinnervation.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous MRI studies focused on localizing pathologic abnormalities in BrS. 6,15,20 While MRI in one prior congenital case showed no change in SO cross-section during vertical gaze shift, 16 no prior study in BrS has analyzed the SO through a large anteroposterior extent of the orbit. The current study showed that the SO muscle had significantly subnormal size bilaterally in congenital cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 An innervational etiology for some cases of congenital Brown syndrome is now also supported since some electromyographic studies revealed paradoxical innervation of superior oblique muscle in some patients with absence of trochlear nerve but non hypoplastic or atrophic superior oblique muscle. 8,9 The size of the muscle remained constant during vertical eye movements, suggesting no relaxation of it in upgaze. This finding can be explained by the existence of anomalous innervation of the superior oblique muscle by fibers of the third cranial nerve intended either for the medial rectus or inferior oblique muscle.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Otherwise, a dysinnervational Brown syndrome would be expected to persist throughout life.…”
Section: Discussionmentioning
confidence: 99%